Regulatory and Legal Support for the Development of Digital Infrastructure in Rural Areas as a Factor in Improving the Level of Sustainable Development and Quality of Life of the Rural Population - YDYRYS, Serikbai; IBRAYEVA, Nazgul; ABUGALIYEVA, Fariza; ZHASKAIRAT, Mira; UVALIYEVA, Aiman (Journal of Environmental Management and Tourism, 2023)
Widespread problems of rural development have been the subject of scientific analysis and discussions for many years. The current debate is the result of reflections on improving the effectiveness of rural development policy and the search for new approaches to their development at the local level. They are also the result of the need not only to implement the Sustainable Development Goals more effectively but also to reduce the social and economic inequality between the village and the city, which is possible through the development of the digital infrastructure of rural areas. The purpose of the article is to identify priority areas and institutional and legal barriers to the development of digital infrastructure, the tools necessary to overcome them, and regulatory and legal support for the development of digital infrastructure in rural areas. The article identifies the advantages of digital infrastructure for the socio-economic development of rural areas, the priority level of the introduction of digital infrastructure and technologies for various sectors in the life of the rural population, institutional and legal barriers to the development of digital infrastructure of rural areas, as well as tools of regulatory support for the development of digital infrastructure of rural areas. It is concluded that the creation of the necessary regulatory framework that would stimulate the formation of digital infrastructure while protecting the interests of rural residents is the most significant of the problems of rural areas.